Study of the process of pedestrianization of urban environments in the Historical Center of Cusco. Case of the street of the middle - Alfaro Aucca, Crayla (2023)
The study begins with a critical analysis of the contents oriented to the functional vision of public spaces, mobility and accessibility through territorial planning in the historic center of Cusco, to then delve into similar experiences in other sites of the same condition. Through the application of a mixed methodology, quantitative and qualitative data have been identified based on three variables and categories of study: the physical dimension of the intervention, the social-cultural dimension depending on the intervened space and the economic repercussions that have been given by the change of use of the street. All the data obtained and compared are given as a result of the pedestrianization process between 2006 and 2022. Finally, the results are scopes that occur from the perception of occasional passers-by, frequent users and administrators of buildings destined for different uses whose process also describes and analyzes the proposed research.